Today's Technician: Automotive Engine Performance Classroom and Shop Manual - Pickerill Ken (Thomson Delmar Learning, 2005)
This comprehensive training/education package focuses on the major engine systems affecting engine performance and drivability. Today?s Technician?: Automotive Engine Performance, 4th Edition includes thoroughly updated content on ignition systems, intake and exhaust systems, fuels and emission controls and related electronics, in two comprehensive manuals. With a sharp focus on current technologies and the inclusion of outstanding learning features, this new edition provides an excellent classroom resource for students preparing to become future technicians.